CORPORATE SOCIAL RESPONSIBILITY AS PART OF COMPANY IMAGE MANAGEMENT IN BANKING INSTITUTIONS - Bednarska-Olejniczak, Dorota (Acta Scientiarum Polonorum. Oeconomia, 2016)
The scope and the predominant approaches to corporate social responsibility (CSR) are discussed, as employed by the leading Polish retail banking institutions at present, together with analyses of the impact made by CSR activities upon the business image of banks as institutions of public trust. This study was based on critical analyses of available literature on corporate social responsibility, banking and marketing, and analyses of secondary sources on CSR activities employed by retail banks. Secondary data was obtained from official CSR reports and announcements published on the webpages of selected banking institutions in Poland. The study confirmed the involvement of all banks in CSR-related activities in all four areas specified in the provisions of the ISO 26000 standard and the Global Compact initiative quidelines, namely: responsible approach to customers and markets, activities addressed to employees, support for local communities, and protection of natural environment. The analysis of specialist rankings and official CSR reports seems to confirm the strategic character of the CSR activities employed by the selected representatives of the banking sector.